Fasting Glucose, Creatinine and Total Cholesterol Levels in Normal Individuals: Difference with Age (Community Based Medical Journal, 2025)
Ageing is one of the well-known risk factors for many physiological disorders. This cross-sectional, observational study was carried out in the Department of Biochemistry, Community Based Medical College, Bangladesh (CBMC,B), Mymensingh, Bangladesh, from January to December 2024, from January to December, to see the association between age and the changes in fasting blood glucose, serum creatinine and total cholesterol levels among normal individuals. 100 subjects were included in this study following inclusion and exclusion criteria and categorized in group A (50 adults aged between 24 and 49 years) and group B (50 adults aged between 50 and 78 years). The clinical and historical information was collected through prescribed questionnaires to evaluate the exclusion criteria of the study. Fasting venous blood samples were taken from the subjects with all aseptic precautions. Fasting blood glucose, serum creatinine and total cholesterol were determined by enzymatic method using semi-automatic clinical chemistry analyzer. A significant increase in fasting blood glucose, serum creatinine and total cholesterol were observed in subjects aged above 50 compared to the subjects aged below 50 years (p